2021
DOI: 10.1002/ski2.36
|View full text |Cite
|
Sign up to set email alerts
|

Inspired by vitamin A for anti‐ageing: Searching for plant‐derived functional retinoid analogues

Abstract: Background Cosmetic treatments that inspire one's appearance to resemble their younger portrait often utilize ingredients that confer acute effects, particularly hydration by creating hydrophobic barriers or transient elevation of barrier water content. But superior therapies successfully promote morphogenesis of the dermal‐epidermal junction, inspiring extracellular matrix (ECM) formation. This can be achieved by agonism of the very well‐known retinoid nuclear receptors using the endogenous ligand all‐trans r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
(156 reference statements)
0
5
0
Order By: Relevance
“…Collectively, the results of this first study pinpoint at an induction of genes by HME that shows a similar pattern to that of retinols. Some plant compounds have been shown to induce gene upregulation partially overlapping that of retinol [35]. So far, only bakuchiol, a meroterpene phenol from the seeds of Psoralea corylifolia , was shown to have really a retinol‐like anti‐ageing gene induction profile [15].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the results of this first study pinpoint at an induction of genes by HME that shows a similar pattern to that of retinols. Some plant compounds have been shown to induce gene upregulation partially overlapping that of retinol [35]. So far, only bakuchiol, a meroterpene phenol from the seeds of Psoralea corylifolia , was shown to have really a retinol‐like anti‐ageing gene induction profile [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implied that bakuchiol acts as a functional analogue of retinol [19–21]. Bakuchiol, thus, appears to be a promising alternative to retinol for facial antiageing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Bakuchiol was suggested to exhibit retinol-like functions, as in a skin substitute model, both substances show similar gene expression patterns in vitro [19] and an improvement of cutaneous photodamage in vivo [20]. Hence, it has also been referred to as a plantderived functional retinoid analogue [21]. Further studies demonstrated antioxidant [19,[22][23][24], anti-inflammatory [19,[25][26][27], antibacterial [28] as well as antiproliferative and antitumor effects [29,30] of bakuchiol.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, phytol has also been shown to increase the release of CA 2+ reserves via activation of GPR40, a G-protein-coupled receptor that normally binds to free fatty acids, with an EC 50 of 34.5 µM [ 170 ]. The activation of PPARs, RXRs, and GPR40 by phytol may also be of potential therapeutic benefit for the treatment of diabetes, and because of the ability to activate RXR receptors, phytol is also being pursued by the cosmeceutical industry as an anti-aging treatment in lieu of retinol (which is not well tolerated by all individuals due to its activation of TRPV1) [ 171 , 172 ].…”
Section: Mechanism Of Action For Terpenes—pharmacologic Receptor Targ...mentioning
confidence: 99%